2012
DOI: 10.1089/dia.2012.0160
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone-Based Pattern Recognition and Data Analysis for Patients with Type 1 Diabetes

Abstract: Background: Persons with type 1 diabetes who use electronic self-help tools, most commonly blood glucose meters, record a large amount of data about their personal condition. Mobile phones are powerful and ubiquitous computers that have a potential for data analysis, and the purpose of this study is to explore how self-gathered data can help users improve their blood glucose management. Subjects and Methods: Thirty patients with insulin-regulated type 1 diabetes were equipped with a mobile phone application fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Similar to previous finding in the illness and disability literature [21][22][23][24][25][26][27], including SCI [14][15][16][17][18][19][20], the use of IT in our sample was found to have implications for the management of their health. Specifically, participants commented that they sought information online with regards to accessing information regarding SCI, which has been found to be this population's preferred source for health-related information [33].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to previous finding in the illness and disability literature [21][22][23][24][25][26][27], including SCI [14][15][16][17][18][19][20], the use of IT in our sample was found to have implications for the management of their health. Specifically, participants commented that they sought information online with regards to accessing information regarding SCI, which has been found to be this population's preferred source for health-related information [33].…”
Section: Discussionsupporting
confidence: 88%
“…This is best illustrated through a number of studies examining how access to personal IT can promote health in those with diabetes mellitus. Studies have shown that access to mobile phones, text messaging, online video-conferencing and social networking can improve the health of diabetics by offering peer support [21], by improving blood glucose monitoring and control [22][23][24][25], providing information resources [26,27], supporting patients' feelings of self-efficacy [25], and improving selfmanagement of health [23,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…The 18 studies included in this review consist of 5 qualitative studies [40][41][42][43][44], 5 experimental studies [31][32][33][34][35], 3 observational studies [28][29][30], 4 cross-sectional studies [36][37][38][39] and 1 mixed methods [45]. Five of the studies were smaller samples drawn from parent clinical trials [29,32,38,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Skrosveth et al [30] explored which methods of diabetes data analysis could be realistically used to provide meaningful feedback for the user. A mobile diary application was developed for adults with T1DM to log insulin doses and dietary intake with options for the user to comment upon these and a screen to visualize each of the following variables BG levels, insulin dosing and dietary intake.…”
Section: Meaningful Feedback For the Usermentioning
confidence: 99%
“…Skrøvseth et al conducted a study to identify how self-gathered data can help users to improve their blood glucose management [61]. The participants were equipped with a mobile phone application, recording blood glucose, insulin, dietary information, physical activity and disease symptoms in a minimally intrusive way.…”
Section: Carbohydrate Estimationmentioning
confidence: 99%